2000
DOI: 10.1086/315162
|View full text |Cite
|
Sign up to set email alerts
|

Immune Responses to Hepatitis C Virus Structural and Nonstructural Proteins Induced by Plasmid DNA Immunizations

Abstract: DNA-based immunizations have been used to elicit cellular immunity to hepatitis C virus (HCV) proteins in mice. Mice were immunized by intramuscular or intradermal injections of plasmid DNA derived from a near-full-length HCV genotype 1b genomic clone (pRC/B2) or individual genomic clones. These immunizations induced cytotoxic T lymphocytes (CTLs), as revealed in standard chromium-release assays that used syngeneic peptide-pulsed or transfected target cells. These assays identified four CTL epitopes within the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
22
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(25 citation statements)
references
References 39 publications
(40 reference statements)
3
22
0
Order By: Relevance
“…Splenocytes from vaccinated mice were pulsed with 10 g of Core, E1, or E2 peptide per ml, corresponding to HCV genotype 1b, which has been previously shown to activate CTLs in immunized BALB/c mice (27,53). As shown in Fig.…”
Section: Vol 76 2002mentioning
confidence: 99%
“…Splenocytes from vaccinated mice were pulsed with 10 g of Core, E1, or E2 peptide per ml, corresponding to HCV genotype 1b, which has been previously shown to activate CTLs in immunized BALB/c mice (27,53). As shown in Fig.…”
Section: Vol 76 2002mentioning
confidence: 99%
“…It has been shown that DNA immunizations can induce both specific antibodies and cell-mediated responses against the structural and nonstructural (NS) HCV proteins in mice. [6][7][8][9][10][11][12][13][14][15][16] The NS protein 3 of HCV has been considered as a possible vaccine target. The reasons for this are that the NS3 protein shows a limited genetic variability, it performs multiple enzymatic functions, and it is a relatively large protein.…”
Section: Introductionmentioning
confidence: 99%
“…However, it is likely that the use of long inserts often leads to both a decrease of gene expression and instability of plasmids during amplification. Although it was reported that a DNA construct encoding a whole HCV polyprotein can induce HCV-specific T-cell responses, those T-cell responses were not directly compared to T-cell responses induced by a mixture of multiple plasmids with shorter-length inserts (16). One of the most critical concerns to be addressed is the relationship between insert length in a plasmid and the strength of induced T-cell responses.…”
mentioning
confidence: 99%